Summer in the spotlight - Johnson, Liz, 1981- (Johnson, Liz, 1981- Prince Edward Island shores, 2023)
"After a devastating hurricane on Prince Edward Island, Kelsey Ahern sets out to save her beloved community theater-and her job. As she draws her friend, Levi Ross, into her plans for a benefit show, she discovers there's more to him than she expected, and that God's plans for their future are so much more important than the struggles of their pasts"--